ENTRE EL LIRISMO Y LA SÁTIRA: LA PRESENCIA DE HORACIO EN LA POESÍA INGLESA MODERNA - Galván Reula, Fernando (Myrtia, 1994)
This essay addresses the issue of Horace's presence in modern English poetry. It does so through a general presentation of Horace's influence in English literature from the Middle Ages to the 20th century, as cuell as through a detailed discussion of the contributions of particular poets of the 16th, 17th and 18th centuries. Among the poets considered are Wyatt, Shakespeare, Ben Jonson, Robert Herrick, Milton, Marvell, Dryden and Pope.